Development of a 3-hydroxypropionate resistant Escherichia coli strain. Issue 1 (2nd January 2016) - Liu, Min; Han, Xueping; Xian, Mo; Ding, Yamei; Liu, Huizhou; Zhao, Guang
ABSTRACT: 3-hydroxypropionate (3HP) is an important platform chemical, and its biosynthesis is severely restricted by the toxicity of 3HP on cell growth and survival. To improve Escherichia coli resistance to 3HP and reduce the total production cost in industrial applications, we have identified variations in protein expression level exposed to sub-lethal concentration of this chemical using 2-dimensional gel electrophoresis. Under 3HP stress, the amount of 46 proteins was increased while the amount of 23 proteins was reduced. According to the proteomic results, overexpression of some identified proteins significantly increased the E. coli survival rate under 3HP stress. This study shed light on clues for developing E. coli strains with higher resistance to 3HP toxicity and lower production cost for industrial applications.